Epigenome-wide association study reveals a molecular signature of response to phylloquinone (vitamin K1) supplementation. Issue 8 (2nd August 2020) - Westerman, Kenneth; Kelly, Jennifer M.; Ordovás, José M.; Booth, Sarah L.; DeMeo, Dawn L.
ABSTRACT: Evidence suggests there are roles for vitamin K in various chronic disease outcomes, but population-level diet and supplement recommendations are difficult to determine due to high levels of variability in measures of status and response to intake compared to other nutrients. In this preliminary investigation, a blood-based epigenome-wide association study (EWAS) comparing responders and non-responders to phylloquinone (vitamin K1) supplementation (NCT00183001) was undertaken in order to better understand the molecular underpinnings of this observed variability. Responders (n = 24) and non-responders (n = 24) were identified in a prior 3-year phylloquinone supplementation trial based on their changes in plasma phylloquinone concentrations. Differential DNA methylation was identified in multiple regions with previously unknown relationships to phylloquinone absorption and metabolism, such as at the TMEM263 locus. A hypothesis-driven analysis of lipid-related genes highlighted a site in the NPC1L1 gene, supplementing existing evidence for its role in phylloquinone absorption. Furthermore, an EWAS for baseline plasma phylloquinone concentrations revealed a strong correlation between the epigenomic signatures of phylloquinone baseline status and response to supplementation. This work can guide future epigenomic research on vitamin K and contributes to the development of more personalized dietary recommendations for vitamin K.